Pemikiran Etika Mohamed Abid Al-Jabiri dan Relevansinya dengan Film Bidaah - Ayyesa Afrilia Zalsabila; Fiqi Restu Subekti; Zuraida Nur Rahmawati (Lembaga Yasin AlSys, 2026)
Although the cultic veneration of religious figures in popular culture has become increasingly widespread, studies that specifically examine the relevance of Mohamed Abid al-Jabiri’s notion of rational ethics for reading ethical representations in popular media remain limited. This study aimed to identify how the Arab ethical values critiqued by al-Jabiri, including Persian, Greek, Sufi, pre-Islamic Arab heritage, and Qur’anic ethics are mobilized in the narrative elements, characterization, and dialogue of the film Bidaah. An interpretive qualitative method was employed, using film text analysis as the primary data source and al-Jabiri’s works as the theoretical foundation. Data collection involved repeated viewing, scene coding, and triangulation of library sources, which were then thematically analyzed to map the ethical configurations presented in the film. The findings indicate that Bidaah exhibits problematic ethical patterns warned against by al-Jabiri, including total submission associated with Persian heritage, a tendency toward elitist rationality reflecting the influence of Greek heritage, and self-annihilating practices in Sufi variants, alongside forms of resistance rooted in Arab chivalric ethics and Qur’anic ethics of good deeds. In conclusion, al-Jabiri’s framework of rational ethics proves relevant for popular culture analysis and is capable of explaining the symbolic and social mechanisms that sustain the cultic elevation of religious figures. The implications of this study include strengthening the theoretical grounding for research in ethical philosophy and film studies, as well as offering practical recommendations for enhancing religious and media literacy and reinforcing the accountability of charismatic figures in the public sphere.